Pengembangan E-LKPD Berbasis Problem Based Learning Menggunakan Aplikasi Flip Pdf Professional Pada Materi Jamur Kelas X SMA - Kukuh Dinda Setiarani; Irda Sayuti; Resma Wahyuni (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to produce Problem Based Learning-based E-LKPD using the Flip PDF Professional application on mushroom material for class X SMA. This research is a Research & Development (R&D) study, which adapts the ADDIE model to the product development stage. This research was conducted at Biology Education, Faculty of Teacher Training and Education, Riau University for trial I and at SMAN 11 Pekanbaru for trial II in August 2024 to May 2025. The data collection instruments used were validation sheets and student response questionnaires. The validation sheet was assessed by 4 validators consisting of 2 lecturers and 2 high school teachers consisting of four aspects, namely content eligibility, language, presentation, and graphics. Based on data analysis, the average score for validation of aspects of content feasibility, pedagogics, language, and presentation on E-LKPD based on Problem Based Learning obtained a score of 3.90 with very valid criteria. While the student response questionnaire trial I obtained a value of 3.54 with very good criteria and the student response questionnaire trial II obtained a value of 3.59 with very good criteria. Based on the results of the study, it can be concluded that the Problem Based Learning-based E-LKPD using the Flip PDF Professional application that has been developed is of very good quality and can be used in learning grade X biology.